2021
DOI: 10.1088/1361-6463/abdefc
|View full text |Cite
|
Sign up to set email alerts
|

BAlN for III-nitride UV light-emitting diodes: undoped electron blocking layer

et al.

Abstract: The undoped BAlN electron-blocking layer (EBL) is investigated to replace the conventional AlGaN EBL in light-emitting diodes (LEDs). Numerical studies of the impact of variously doped EBLs on the output characteristics of LEDs demonstrate that the LED performance shows heavy dependence on the p-doping level in the case of the AlGaN EBL, while it shows less dependence on the p-doping level for the BAlN EBL. As a result, we propose an undoped BAlN EBL for LEDs to avoid the p-doping issues, which a major technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…B x Al 1− x N is highly expected to be useful when applied in the undoped electron-blocking layer (EBL) to overcome the p-doping problem in Al x Ga 1− x N. 17 Therefore, the carrier mobility is quite important to the performance. However, there is a lack of reports on this for B x Al 1− x N alloys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B x Al 1− x N is highly expected to be useful when applied in the undoped electron-blocking layer (EBL) to overcome the p-doping problem in Al x Ga 1− x N. 17 Therefore, the carrier mobility is quite important to the performance. However, there is a lack of reports on this for B x Al 1− x N alloys.…”
Section: Resultsmentioning
confidence: 99%
“…7–13 Replacing the cation with boron, the lightest element of the IIIA group, can also increase the flexibility of applications. 14–17 The B x Al 1− x N/AlN superlattice would enable a high density of two-dimensional electron gas (2DEG) in its layers 14 since wurtzite boron nitride (w-BN) possesses the strongest spontaneous polarization of 2.174 C m −2 (ref. 18 and 19) in III-nitrides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the high-Al content electron blocking layer can be removed from the LED structure without performance degradation. Besides, we reported a highperformance UV LED with a BAlN EBL [7]. BAlN is an emerging ultra-wide bandgap III-Nitride semiconductor.…”
Section: Technical Summarymentioning
confidence: 99%
“…10 The energy band can also be modulated by employing various materials and structures. Wen et al proposed an undoped B 0.14 Al 0.86 N EBL to significantly improve electron blocking and hole injection, 11 and Liu et al used InAlN as the LQB to modulate the polarization charge and band bending at the LQB/EBL. 12 Ren et al revealed that the EBL could be removed in DUV LEDs using a composition-grade quantum barrier.…”
Section: Introductionmentioning
confidence: 99%